Evaluating Vitamin E's Antioxidative Effect on Carbamazepine-Induced Spleen Damage in Rat Models - Asma Basharat Ali; Nadia Younus; Sahrish Mukhtar; Lubna Faisal; Tayyaba Kazmi; Alina Atif (ziauddin University, 2024)
Background: The spleen is essential for the body's homeostasis and immune system. Carbamazepine (CBZ) is known to cause toxicity to several organs, including the spleen, through oxidative stress, however, vitamin E (Vit E) is a proven antioxidant against toxins. Thus, this study evaluated the antioxidative effect of Vit E on hematological and splenic toxic changes, caused by carbamazepine in rats. Methods: This in-vivo preclinical experimental study was conducted from March-June 2020, at Jinnah Medical and Dental College, Karachi. Forty adult male rats, weighing 150-200 grams were included and randomly divided into 4 groups. Group I was control; Group II received oral Carbamazepine (50mg/kg/day), Group III received Carbamazepine (50mg/kg/day) with Vit E (200mg/kg/day), and Group IV received Vit E (200mg/kg/day) daily. After 6 weeks, animals were sacrificed, blood samples were drawn and splenic tissue was processed for morphological examination. SPSS version 22 was used, and ANOVA was applied to investigate the difference of means with p≤0.05 considered significant. Results: Our findings showed that Group II rats had significantly decreased final body weights, and absolute and relative spleen weights compared to control. Lower hemoglobin, lymphocytes, and platelets, and significantly increased TLC and neutrophils were observed in Group II compared to control and Group IV. Histology showed a thickened capsule, reduced white pulp, and congested red pulp in Group II spleens whereas these toxic effects were reduced in Group III. Conclusion: Our study demonstrated that the hematologic and splenic toxic effects of carbamazepine were lessened significantly with the antioxidative properties of vitamin E. Keywords: Carbamazepine, Vitamin E, Spleen, Oxidative Stress, Hematology.